FAKTOR PENYEBAB ANAK BEKERJA DI DAPUR BATU BATA DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Kiki Maria Maria; Daeng Ayub Natuna Ayub Natuna; Desti Irja Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The work has become a necessity for an adult or child bearing age, let alone a normal person disabled fisikpun need a job according to his ability. In the village of Binjai, background people's lives most of earning a living to make ends meet everyday family as a kitchen worker at a brick. Because of the economic factors that are less able to also make the cause of many children who are forced to drop out of school due to the higher costs incurred by his parents to pay school fees this childerns.Other that, due to the large number of children in the family to be borne by parents, so parents realize their plans to meet their daily needs, so that the absence of the ability of parents to educate their children as where like kids who basically have to have a minimum of 9 years of education as defined by the government. The purpose of this study is, to determine the factors causing children to work in the kitchen brick in the Village District of Tenayan Kingdom Kulim Pekanbaru, to find out what drives children to work in the kitchen of bricks, to determine whether the income from child work sufficient to cover subsistence days, to determine whether the work is influential on children's achievement in school, to find out if a child working in a brick kitchen according to their own desires. From all descriptions in this thesis research, the researchers tried to give a conclusion as the essence of the research that people in the village of Binjai is still relatively disadvantaged families resulting parents could not afford their children to school, so that the interests of children and the high school dropouts schools are looking for other alternatives to help the economy parents and school fees by becoming a brick kitchen worker. Keywords: Factors causing, child work, brick kitchen.